Mechanism of electric potential trap formation due to inject of electron beam into a uniform magnetic field - Bizyukov, A.A.; Volkov, E.D.; Tarasov, I.K. (Вопросы атомной науки и техники, 2000)
The mechanism of non-neutral electron plasma accumulation and confinement during injection of widely spread in longitudinal velocity electron beam into a drift tube in a strong uniform magnetic field was studied experimentally. The properties and the formation of collective electron trap for electron beam that propagates in conducting cylinder are described in this paper. It is shown that the electron beam provides the development of an instability in the above mentioned conditions. The instability leads to the formation of electric potential trap. The trap captures electrons during the formation and keeps them inside the drift tube